Which kind of miniplate to use in mandibular sagittal split osteotomy? An in vitro study - Ribeiro-Junior, P. D.; Magro Filho, Osvaldo [UNESP]; Shastri, K. A.; Papageorge, M. B. (Churchill Livingstone, 2012)
This study verified the resistance to displacement of six miniplate fixation methods after sagittal split osteotomy (SSO). SSO was performed in 30 polyurethane synthetic mandible replicas. The distal segments were advanced (4 mm) and specimens were grouped according to the fixation method: four-hole standard miniplate; four-hole locking miniplate; six-hole standard miniplate; six-hole locking miniplate; six-hole standard sagittal miniplate; six-hole locking sagittal miniplate. Biomechanical evaluation was performed by applying compression loads to three points on the second molar region, using an Instron universal testing machine until a 3 mm displacement of the segments occurred. Compression loads able to produce 3 mm displacement were recorded in kN and subjected to analysis of variance (P < 0.01) and Tukey's tests for comparison between groups (P < 0.05). The locking sagittal miniplate showed higher resistance to displacement than the regular four- and six-hole locking and standard miniplates. No significant differences were observed between the locking sagittal miniplate and the regular sagittal or the four-hole locking miniplates. Two of the three groups with the best results had locking plate fixation methods. Fixation of SSO with a single miniplate is better accomplished using six-hole locking sagittal miniplates, six-hole standard sagittal miniplates, or four-hole locking miniplates; these methods are more resistant to displacement.
Keywords: rigid internal fixation; mandibular bilateral sagittal split osteotomy; bone plate